The Action Research Planner - Kemmis, Stephen; McTaggart, Robin; Nixon, Rhonda (Springer, 2014)
that began in 1979 with a modestly produced version for education students at Deakin University in Geelong Australia. A course was offered as part of an ‘upgrading’ Bachelor of Education degree designed for practising teachers. The intention was to encourage teachers to conduct small action research projects, or preferably, to participate in larger ones, and to report regularly on their action research work and reading throughout the year through a course journal. Each student was also expected to write a critical review of another student’s work, and on an aspect of the action research literature. The early Planners were somewhat restricted by their need to guide assessment tasks required by a course. Nevertheless, the Planners became popular and were used in many projects in several professional fields and community projects outside Deakin University, with varying degrees of success. As the Planners began to be used by a wider readership and without the support of other readings prescribed for the Deakin Action Research course, we re-worked the text to give a little more theoretical background and to take account of the growing literature discussing more critical approaches to action research, including Carr and Kemmis (1986) which had also begun its life as a text for students in the Deakin Action Research course. Twenty-first century volumes of the SAGE Handbook of Qualitative Research presented more refined versions of the idea of critical participatory action research (Kemmis and McTaggart 2000, 2005). These chapters described significant reconsideration of the concepts of educational practice, research practice, and participation. This twenty-first century thinking shapes the intention of this version of The Action Research Planner with its new sub-title Doing Critical Participatory Action Research.
Doing Critical Participatory Action Research